2008
DOI: 10.1080/09546630802032595
|View full text |Cite
|
Sign up to set email alerts
|

A case of granulomatous rosacea successfully treated with pimecrolimus cream

Abstract: A 43-year-old male attended with lesions on his face that had been present for 3 months. On dermatological examination, multiple papules and pustules were seen on the forehead, nose, bilateral cheeks and lower eyelids. The patient used systemic clindamycin and doxycycline and topical benzoyl peroxide therapies, but the lesions did not regress. Routine laboratory tests were normal. Histopathological examination of the lesions confirmed the diagnosis of granulomatous rosacea. Pimecrolimus cream 1% was applied to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0
1

Year Published

2011
2011
2015
2015

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 7 publications
0
5
0
1
Order By: Relevance
“…23 There are 2 case reports of the use of pimecrolimus 1% cream applied to lesions twice a day with good efficacy. 34,35 One patient used pimecrolimus 1% topical cream combined with sun block twice a day resulting in complete resolution of lesions after 4 months of therapy. 35 The other patient responded well to pimecrolimus 1% cream after failing a 45-day course of topical metronidazole and oral doxycyline.…”
Section: Evaluation and Managementmentioning
confidence: 99%
See 1 more Smart Citation
“…23 There are 2 case reports of the use of pimecrolimus 1% cream applied to lesions twice a day with good efficacy. 34,35 One patient used pimecrolimus 1% topical cream combined with sun block twice a day resulting in complete resolution of lesions after 4 months of therapy. 35 The other patient responded well to pimecrolimus 1% cream after failing a 45-day course of topical metronidazole and oral doxycyline.…”
Section: Evaluation and Managementmentioning
confidence: 99%
“…34,35 One patient used pimecrolimus 1% topical cream combined with sun block twice a day resulting in complete resolution of lesions after 4 months of therapy. 35 The other patient responded well to pimecrolimus 1% cream after failing a 45-day course of topical metronidazole and oral doxycyline. 34 There was no evidence of relapse after stopping the medication.…”
Section: Evaluation and Managementmentioning
confidence: 99%
“…4,5 In contrast, data from noncontrolled settings suggest a benefit associated with pimecrolimus therapy, including one study that demonstrated comparable efficacy to topical metronidazole 1% cream. 69 National guidelines and international consensus statements on rosacea management recognize the varying levels of evidence associated with the use of this topical agent and state that further evidence is needed to provide conclusive support for use. 10,11…”
Section: Resultsmentioning
confidence: 99%
“…Isolated case reports have documented the effectiveness of pimecrolimus 1% cream in adult patients with refractory rosacea. 8,9…”
Section: Resultsmentioning
confidence: 99%
“…En una serie de casos se encontró disminución del eritema, de las lesiones inflamatorias y del edema, sin cambios en las telangiectasias, en rosácea pápulo-pustular y eri-temato-telangiectásica 89 . En dos reportes de casos se evaluó su efectividad en la rosácea granulomatosa, obteniéndose excelente resultado, sin recaídas a los seis meses de suspender el tratamiento 90,91 .…”
Section: Pimecrolimus Como Monoterapiaunclassified